Contrasting outcomes of species‐ and community‐level analyses of the temporal consistency of functional composition. Issue 9 (1st September 2017) - Katabuchi, Masatoshi; Wright, S. Joseph; Swenson, Nathan G.; Feeley, Kenneth J.; Condit, Richard; Hubbell, Stephen P.; Davies, Stuart J.
Abstract: Multiple anthropogenic drivers affect every natural community, and there is broad interest in using functional traits to understand and predict the consequences for future biodiversity. There is, however, no consensus regarding the choice of analytical methods. We contrast species‐ and community‐level analyses of change in the functional composition for four traits related to drought tolerance using three decades of repeat censuses of trees in the 50‐ha Forest Dynamics Plot on Barro Colorado Island, Panama. Community trait distributions shifted significantly through time, which may indicate a shift toward more drought tolerant species. However, at the species level, changes in abundance were unrelated to trait values. To reconcile these seemingly contrasting results, we evaluated species‐specific contributions to the directional shifts observed at the community level. Abundance changes of just one to six of 312 species were responsible for the community‐level shifts observed for each trait. Our results demonstrate that directional changes in community‐level functional composition can result from idiosyncratic change in a few species rather than widespread community‐wide changes associated with functional traits. Future analyses of directional change in natural communities should combine community‐, species‐, and possibly individual‐level analyses to uncover relationships with function that can improve understanding and enable prediction.